(untitled) (World Economics and Finance Bulletin, 2026)
This article provides a scientific and practical analysis of the essence and key directions of digitalization processes in Uzbekistan’s textile industry, as well as their role in enhancing the sector’s export competitiveness. The study examines the impact of the “Textile 4.0” concept, automated production lines, ERP and SCM management systems, IoT and Big Data technologies, ecommerce platforms, international certification requirements, and national brand policy on the development of the textile industry. In addition, the article explores international experience in the digital transformation of the textile sector and the expansion of export potential, substantiating the possibilities of applying this experience in the context of Uzbekistan. The article also analyzes existing reserves in production automation, increasing R&D expenditures, strengthening brand recognition, and diversifying export markets, and develops practical recommendations aimed at improving the competitiveness of the textile industry